Knowledge in Manuscript Writing and Readiness to Conducting Research among Selected Accounting Students - John Mark Asio (Formosa Journal of Multidisciplinary Research, 2023)
This study aims to determine the knowledge of manuscript writing and the readiness among selected accounting students to conduct research from a tertiary institution in Olongapo City, Philippines. The study used a descriptive-correlation research design to 70 purposively chosen students. The data underwent descriptive and inferential measures with the help SPSS 23 software. The study found that students were "knowledgeable" of the different parts of manuscript writing and were "ready" to conduct research. There was also a significant relationship between the knowledge of manuscript writing and the readiness of the students to conduct research. Writing the results and discussion part of the study was a significant predictor to conduct research. Implications for the institution, faculty, and students were suggested.